Gender diversity and financial performance in financial services companies. - Álvarez Morán, Viviana Patricia; Rosas-Rodríguez, Beatriz (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To analyze the effect that female participation on boards of directors has on the ROE and ROA of financial companies listed on the Mexican Stock Exchange, as well as to determine the change in gender diversity.MATERIAL AND METHOD: A sample of financial services companies listed on the Mexican Stock Exchange in the period 2015-2023 was used. A multiple linear regression model was applied, as well as a test of difference of means.RESULTS: Female representation has increased progressively during the period analyzed. In addition, gender diversity has a positive and statistically significant effect on ROA, suggesting profitability advantages in companies with greater female inclusion, while it has no significance in financial performance.CONCLUSIONS: They provide relevant evidence to the discussion on the importance of new corporate governance practices and support guidelines aimed at increasing the percentage of female staff on boards of directors.
Keywords: financial performance; corporate governance; gender diversity; financial companies.